Evaluating Adopt-ability of Open Source Tools for Problem Solving in Specific Design Tasks in Industrial Design Education - Erkarslan, Onder; Aykul, Zeynap (Design and Technology Education: An International Journal, 2023)
The purpose of the study was to evaluate the adoptability of Open Source Tools (OST) as a learning strategy in undergraduate Industrial Design (ID) education. OST has the potential for students to overcome certain difficulties in specific tasks, such as design presentation, design research, design decision, concept generation and design documentation. In this study, both quantitative and qualitative methodologies are used to develop the research. As the first step of the research, quantitative methodology is employed, using a survey method to collect data from students. The survey investigates industrial product design students’ perceptions of difficult tasks and their reasons, as well as their awareness of OST. In the second phase of the study, qualitative methodology is followed to acquire feedback on the proposal regarding Open Source (OS) use in an ID studio course using case studies. The simulation follows qualitative methodology, using primarily observations and obtaining verbal feedback. The results indicated that students were willing to adopt OST as an effective design tool and to overcome difficulties in the design process.